(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: Enterococcus is a nosocomial infection that has become more prevalent due to its innate resistance to conventional antibiotics and recent acquisition of resistance to other current therapeutic alternatives. Aim- Detection of vancomycin-resistant Enterococcus in clinical settings in a tertiary care hospital. Objective- The main objective of this study is to isolate and identify the antimicrobial susceptibility test pattern of the Enterococci from different samples and detect Vancomycin-resistant Enterococcus among the isolated Enterococci strains. Material & Method: This study was conducted in the Bacteriological Section, Microbiology department, Teerthanker Mahaveer Medical College, Moradabad, from November 2023 to July 2024. Enterococcus isolates from clinical samples received in the department of microbiology were included in the study. Isolates were identified and standard methods were used to determine the species. The antibiotic susceptibility test was done using Kirby Bauer’s disc diffusion method. Vitek compact system was used to assess vancomycin’s resistant & sensitive pattern. Result- 135 isolates were identified as Enterococcus from 1677 clinical samples like pus, urine, blood, body fluid, and foley’s tip where 25 (18.5%) were resistant to vancomycin. The maximum age was 61-80 years and the minimum age was 18-20, from whom the isolates were discovered, among which females were 49 and males were 86. Enterococcus faecalis shows 16.2% resistance to the drug Vancomycin whereas Enterococcus faecium shows 24.5% resistance to the drug, whereas other species of Enterococcus found 100% sensitivity to the drug Vancomycin. Conclusion- We conclude that infection control practices and active surveillance must be implemented. According to the prevalence data of Vancomycin-resistant Enterococcus, infection control measures must be strictly followed to prevent the spread of these infections. To reduce the Vancomycin-resistant Enterococcus rate, clinicians should be aware of this rising trend and put strict antibiotic policies and infection control protocols in place.